2015
DOI: 10.1111/cen.12847
|View full text |Cite
|
Sign up to set email alerts
|

Optimum position of left adrenal vein sampling for subtype diagnosis in primary aldosteronism

Abstract: In view of its better potential diagnostic accuracy, technical ease, lower cost and lower risk of vein rupture, blood sampling from the common trunk of the left adrenal vein may be preferable as the standard method of AVS in patients with PA, although additional studies in a larger number of cases are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…As expected, the SI was significantly lower on the left side, which results from the LAV anatomy that joins the inferior phrenic vein forming a common trunk where the catheter is usually placed and aspirates diluted blood. Previous reports indicated that selective cannulation of the LAV does not provide additional benefit [24,25]. The selectivity indices were remarkably high because all procedures were performed during cosyntropin infusion.…”
Section: Discussionmentioning
confidence: 97%
“…As expected, the SI was significantly lower on the left side, which results from the LAV anatomy that joins the inferior phrenic vein forming a common trunk where the catheter is usually placed and aspirates diluted blood. Previous reports indicated that selective cannulation of the LAV does not provide additional benefit [24,25]. The selectivity indices were remarkably high because all procedures were performed during cosyntropin infusion.…”
Section: Discussionmentioning
confidence: 97%
“…The protocol for AVS has been described previously . Cosyntropin was administered by bolus, by continuous infusion or by bolus and continuous infusion.…”
Section: Methodsmentioning
confidence: 99%
“…23 Briefly, cosyntropin was given as a bolus infusion before cannulation in 5 centers, and by a bolus infusion followed by a continuous infusion throughout the procedure in the remaining centers. Catheter cannulation was performed using the percutaneous femoral vein approach.…”
Section: Adrenal Venous Samplingmentioning
confidence: 99%